Using corpora to reveal style in translation: The case of The Song of Everlasting Sorrow - Meng, Lingzi; Pan, Feng (Frontiers in Psychology, 2022)
This article reports on a corpus-based study of the English translation of Wang Anyi’s award-winning novel, The Song of Everlasting Sorrow [长恨歌, Chang Hen Ge] from the perspective of style. Using the keyword and concordance functions of corpus software packages AntConc and ParaConc, this research focuses on how the translator’s style reveals itself in the target text (TT) as well as how the style of the source text (ST) is represented in the TT. Findings show that the translators have a preference for contracted negative verb forms and expressions such as “bit” over “little,” making the text more colloquial. In general, the rendering of the ST style tends not to be entirely faithful. A distinction between reader-centered and text-centered keywords is made. While the reader-centered ST keywords are, as expected, largely altered, the translation of text-centered ST keywords is also rewritten, contrary to expectations. Presumably, the translators tended to reduce the ambiguity of the ST, resulting in a more explicit TT. The article argues that the translators chose to rewrite the translation to make it more understandable for the target audience since it concerned a work from a source culture very different from the target culture.